Pengenaan pajak terhadap jasa peer to peer lending dalam perusahaan fintech - Rahmadanti, Akmila Aning (Maliki Interdisciplinary Journal, 2023)
This article aims to analyze and discuss in more depth how taxes are applied in financial technology companies that provide digital loan services which is P2P Lending. This analysis refers to the Tax Harmonization Law Number 7 of 2021 and Minister of Finance Regulation Number 69 of 2022. The application of taxes to financial technology companies is critical to discuss because of increasingly dynamic developments. To align the progress of the times with economic developments in Indonesia, it is necessary to make changes in every part, such as tax regulations must continually be updated. With this article, it is hoped that all economic actors in Indonesia, especially MSMEs (Micro, Small, and Medium Enterprises), will be able to develop their businesses through digital loans as much as possible.